Management of Nematodes with Cowpea Cover Crops - Zane Joseph Grabau; Esteban Rios (EDIS)
Cover crops are grown between cash crop cycles, or intercropped with cash crops to cover the ground, such as in vegetable fields, orchards, groves, and agricultural sites. If used appropriately, cover crops can improve soil structure and fertility, decrease soil erosion, provide foliage and animal feed, and suppress crop pests such as weeds, insects, nematodes, and other plant pathogens. Residues from cover crops can be incorporated as green manure to supply nutrients and improve fertility for the next crop. Using cover crops can increase on-farm crop diversity, may enhance many beneficial organisms, and possibly even contribute to carbon sequestration. One good example of a summer cover crop is cowpea, Vigna unguiculata (L.) Walp, due to its fast establishment, abiotic and biotic stress tolerance, and biomass production.  This publication is intended to guide agricultural professionals in the use of cowpea cover crops for managing plant-parasitic nematodes.